2016
DOI: 10.1111/nmo.12806
|View full text |Cite
|
Sign up to set email alerts
|

Depleted interstitial cells of Cajal and fibrosis in the pylorus: Novel features of gastroparesis

Abstract: In gastroparetic patients, ICC loss in the pylorus is twice as common as in the antrum and fibrosis in the pyloric smooth muscle is nearly three times more common than the antrum. These findings can provide one explanation for pyloric dysfunction which is a contributing factor to the pathophysiology of gastroparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 28 publications
(79 reference statements)
8
42
0
Order By: Relevance
“…This study and previous studies by the same authors have found similar ICC loss in gastric antrum in patients with GP and GLS [9]. As pointed out by Wang et al, an older study in dogs demonstrated antral contractile forces open the pylorus [13,14].…”
Section: Interstitial Cells Of Cajalsupporting
confidence: 89%
See 1 more Smart Citation
“…This study and previous studies by the same authors have found similar ICC loss in gastric antrum in patients with GP and GLS [9]. As pointed out by Wang et al, an older study in dogs demonstrated antral contractile forces open the pylorus [13,14].…”
Section: Interstitial Cells Of Cajalsupporting
confidence: 89%
“…Significant heterogeneity exists among studies examining the number of ICC in the gastric antrum. Few studies have investigated ICC networks in the pylorus, with only one other human study to date (conducted by the current study's author) [9][10][11].…”
Section: Interstitial Cells Of Cajalmentioning
confidence: 99%
“…; Bashashati & McCallum, ; Farrugia, ; Moraveji et al . ). It has also been shown that different splice variants of Ano1 exist in patients with diabetic gastroparesis and that these variants alter the electrophysiological properties of this ion channel, including sensitivity to intracellular Ca 2+ and CaCC inhibitors (Mazzone et al .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, loss of ICC and smooth muscle fibrosis is more common in the pylorus than in the antrum of patients with refractory GP. 23 The advent of the endoscopic functional luminal imaging probe (EndoFLIP) has allowed for the evaluation of pyloric dysfunction in DMGP. Symptoms of early satiety and postprandial fullness are inversely correlated with the diameter and cross-sectional area of the pyloric sphincter.…”
Section: Introductionmentioning
confidence: 99%